2011
DOI: 10.1007/jhep01(2011)075
|View full text |Cite
|
Sign up to set email alerts
|

M-theory and seven-dimensional inhomogeneous Sasaki-Einstein manifolds

Abstract: Seven-dimensional inhomogeneous Sasaki-Einstein manifolds Y p,k (KE 4 ) present a challenging example of AdS/CFT correspondence. At present, their field theory duals for KE 4 = CP 2 base are proposed only within a restricted range 3p/2 ≤ k ≤ 2p as N = 2 quiver Chern-Simons-matter theories with SU (N ) × SU (N ) × SU (N ) gauge group, nine bifundamental chiral multiplets interacting through a cubic superpotential. To further elucidate this correspondence, we use particle approximation both at classical and quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…We can also apply to inhomogeneous Sasaki-Einstein manifolds, for example, Y p,k CP 2 [26,42]. The operator counting method was studied in [34] and successfully reproduced the volume of Y p,k CP 2 [50] using the AdS/CFT dictionary found in [51]. We expect that the monopole operator plays an important role in this case.…”
Section: Discussionmentioning
confidence: 95%
“…We can also apply to inhomogeneous Sasaki-Einstein manifolds, for example, Y p,k CP 2 [26,42]. The operator counting method was studied in [34] and successfully reproduced the volume of Y p,k CP 2 [50] using the AdS/CFT dictionary found in [51]. We expect that the monopole operator plays an important role in this case.…”
Section: Discussionmentioning
confidence: 95%
“…Since this solution is BPS the classical quantities are exact at quantum level, and one can establish a mapping between the global charges in field theory and the angular momenta of the geodesic motion [33]. It turns out that x = 1 orbits are dual to the operators without the monopole operator.…”
Section: A Non-chiral Model : Dual Abjmmentioning
confidence: 96%
“…Because the quiver diagram Fig.4 does not have obvious symmetry other than flavor SU (3), it is not clear what is the right R-charge assignment. But it turns out that from classical particle motion one can read off simple relations between the R-charge of various fields [33]. We consider a particle moving along the Reeb vector direction, i.e.…”
Section: A Non-chiral Model : Dual Abjmmentioning
confidence: 99%
“…Figure 5(a) shows the presence of qualitatively new "horizontal solutions" in the r − n s plane. If we drop all the α-dependent terms in the scalar potential (9) except the global term linear in α (which is −8α κ s c 3 m 2 x 3 ), the number of horizontal solutions in this region increases. On the other hand, dropping this term and keeping the others does not…”
Section: B the Effect Of The Parameters On The Modelmentioning
confidence: 99%
“…This is somewhat disfavored, although it is within the 2σ bounds, n s = 0.971 ± 0.010 [5]. However, the addition of a linear soft-SUSY breaking term [6] reduces n s significantly [7]; this term is also important in explaining the MSSM µ-problem [8][9][10]. It has been shown that small gravity waves (tensor-to-scalar ratio r) are produced with minimal Kähler (retaining the lowest-order SUGRA term), radiative corrections, and positive soft mass squared and negative linear soft-SUSY breaking terms in the potential.…”
Section: Introductionmentioning
confidence: 99%